Role of the socio-entrepreneur in the construction of safe latrines for community development in east Java, Indonesia - URIPAN, KOEN IRIANTO; MA’RUF, ANWAR; HADI, CHOLICHUL; SUAEDI, FALIH (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The purpose of this article was to analyze the role and existence of safe latrine sociopreneur to building community development in East Java Province based on case studies. Judging from the type of data, the research approach used in this study was a qualitative approach. It was concluded that the process of implementing community empowerment programs carried out by safe latrine sociopreneur to improve health and accessed sanitation in the East Java province with the implementation instructions and technical instructions, was made through 5 community empowerment strategies, namely: enabling, strengthening, protection, support, and maintenance. RESUMEN El propósito de este artículo fue analizar el papel y la existencia de socioempresarios de letrinas seguras para construir el desarrollo comunitario en la provincia de Java Oriental basado en un estudio de caso. A juzgar por el tipo de datos, el enfoque de investigación utilizado fue un enfoque cualitativo. Se concluyó que el proceso de implementación de programas de empoderamiento comunitario llevados a cabo por socioempresarios de letrinas seguras para mejorar la salud y el acceso al saneamiento en la provincia de Java Oriental con las instrucciones de implementación de técnicas, se realizó a través de 5 estrategias de empoderamiento comunitario, a saber: habilitación, fortalecimiento, protección, apoyo y mantenimiento